PELATIHAN PENGGUNAAN APLIKASI KEUANGAN UNTUK MEMAKSIMALKAN PENGELOLAAN UMKM DI KECAMATAN BRANG ENE KABUPATEN SUMBAWA BARAT - Mulawarman, Logi; Prasetyo, Rahman (JUAN: Jurnal Pengabdian Nusantara, 2024)
This training is a Community Service (PKM) activity which was carried out on September 22nd 2023 by Lecturers of Bumigora University, Digital Business Study Program. The PKM team saw that MSME managers in Brang Ene District, West Sumbawa Regency were still facing difficulties in managing finances, business and utilizing technology. Thus, the Team decided to conduct training on the use of financial applications to maximize MSME management. The results show that this training has been effectively implemented. By using financial applications such as Kasvlo and Sribuu, MSME managers can manage their business and finances easily. The two financial applications above are considered very easy to use for MSMEs and can help MSME to increase operational efficiency, reduce risk, and create a more solid foundation for sustainable business growth.